AN ANALYSIS OF ECONOMIC GROWTH IN INDONESIA A NEW PARADIGM - Carolyn Currie (Indonesian Management and Accounting Research, 2013)
Analyses of the nature of debt relying on the theory of rational expectations conclude that the burden of public debt need not fall on future generations if the present generation anticipates the higher taxes needed in the future for debt servicing. However, there have been many instances where increases in budget deficits have been followed by a decrease in the savings propensity of the private sector. Foreign exchange earnings also have to be set aside. It appears that the main problem for countries in an early stage of economic development, is that often the borrowings have not been productively employed so that a national debt crises results. Foreign lenders become increasingly reluctant to lend further amounts to a country, which has been a net capital importer. This paper puts forward a methodology of testing a new theory of economic growth using Indonesia as a case study, as it represents a case of faltering economic growth and financial instability resulting in a huge increase in foreign debt, a depreciating currency and a dramatic increase in the percentage of population below the poverty line. The theory emphasises key factors determining the success or failure of policies that change underlying economic structures, and hence would lead to an intrinsic monitoring of “overborrowing”.JEL classification: L33; O11; O38; O47; P11; P52Key Words: Economic Growth. Debt Burden, Regulation, Ownership Structures